Strain-hardening magnesium-silicate-hydrate composites (SHMSHC) utilizing reactive magnesia cement (MgO) and calcined clay (metakaolin) - Kumar, Dhanendra (2024)
This study demonstrated the feasibility of utilizing calcined clay (metakaolin) as a silica source for the development of polyethylene (PE) fiber-reinforced strain-hardening magnesium-silicate-hydrate composite (SHMSHC). The study also discussed the effects of variation in the Mg/Si ratio of the mixture when pure silica source (silica fume with SiO2 content >90 %) is replaced with metakaolin (SiO2 content ⁓ 51 %) on the mechanical performance of SHMSHC. A comprehensive mechanical characterization of SHMSHC at composite scale and fiber-matrix interaction effects was conducted. The damage characterization was carried out using residual crack width and spacing analysis. The chemical characterization of the MSH matrix (SHMSHC without fibers) was performed using XRD, TGA, and FTIR, and the microstructural investigation was done using FE-SEM. The MgO-metakaolin paste based SHMSHC showed compressive strength of 51.9 MPa, tensile strength of 5.0 MPa, and tensile strain capacity of 4.7 %, demonstrating the feasibility of calcined clay utilization in SHMSHC. The tensile strain capacity was reduced after the addition of aggregates in SHMSHC. The study demonstrated that the variation in the Mg/Si ratio significantly affects the toughness of the MSH matrix and fiber-matrix interaction characteristics, influencing the strain-hardening potential of SHMSHC.